Impact of land use and land cover change on the landscape pattern and service value of the village ecosystem in the karst desertification control - Wang, Qi; Xiong, Kangning; Zhou, Jiayi; Xiao, Hua; Song, Shanhai (Frontiers in Environmental Science, 2023)
Human activities have had a significant impact on ecosystems. Studying landscape patterns and ecosystem services (ES) at the village scale based on land use and land cover (LULC) is essential in addressing current ecosystem issues. Based on GF images, the paper selects village ecosystems of karst desertification control (KDC) as the research object. It uses the landscape pattern index, topographic position index (TPI), and value equivalent method to conduct a spatial and temporal analysis of the ecosystem service value (ESV) of the karst desertification control cycle (2015–2020). The results show that: 1) forest land, orchard land, and construction land increase, and dryland and grassland decrease. The landscape shows an aggregated state, with spreading and connectivity increasing while fragrant diversity is decreasing. 2) The total ecosystem service value increased by CNY 63.45 × 104, with regulating and cultural services on the rise and supply and support services on the decline. 3) With the rise of the TPI, the value of the supply services is inversely U-shaped, while the value of the remaining services increases. This study provides a case study about karst desertification areas for village-scale ecosystem services research.